VMInformant: an instrumented virtual machine to support trustworthy cloud computing. (2015) - Al-Said, Taimur; Rana, Omer; Burnap, Peter
We describe how a virtual machine (VM) owner can increase visibility about how a VM and its data are stored and processed in the cloud. We present 'VMInformant', a monitoring system which can keep the user informed about events that take place on their VM (both inside the VM and via calls made through a hypervisor). A taxonomy of VM security-related events is presented, along with performance overheads associated with monitoring such events using CPU and I/O intensive benchmarks. We argue that having this level of transparency is essential to improve trust between a cloud consumer and provider.